Tradisi Mangundu Mantu Masyarakat Tanamon dalam Konsepsi Hukum Islam - Rizky Ayub S. Biya; Rosdalina Bukido (Al-Mujtahid: Journal of Islamic Family Law, 2023)
This article discusses the mangundu mantu custom from the perspective of Islamic law in Tanamon Village, Sinonsayang District, South Minahasa Regency. The main problem is how are the customary procession of mangundu mantu in Tanamon Village and the view of Islamic law regarding the mangundu mantu custom from the perspective of Islamic law. This study uses descriptive qualitative research methods where researchers will go directly to the field to conduct interviews, observations, and documentation with those who know and understand the mangundu mantu custom and what Islamic law’s perspective is regarding the mangundu mantu business in Tanamon Village, Sinonsayang District, South Minahasa Regency. The research results in this thesis discuss the custom of mangundu mantu, a ceremony for welcoming the bride who comes to the house or sabuah (canopy as a gathering place for the groom's family). In carrying out the wedding procession for the Bantik community in Tanamon Village, the main party is held at the bride's house. After that, the bride and groom (both women and men) go to the groom's house, if the house is far away, they can use a vehicle, but at a distance of approximately 200 meters, the bride and groom must go down together with the bridal procession. Then wait for the groom's family to take turns pulling the bride by shaking hands and giving gifts in the form of money or other valuables and walking step by step until they are correct at the entrance to the groom's house. Keywords: Islamic law; Mangundu Mantu; Tradition. ABSTRAK Artikel ini membahas tentang adat mangundu mantu dalam perspektif hukum Islam di Desa Tanamon Kecamatan Sinonsayang Kabupaten Minahasa Selatan. Masalah utamanya adalah bagaimana prosesi adat mangundu mantu di Desa Tanamon serta pandangan hukum Islam tentang adat mangundu mantu dalam perspektif hukum Islam. Dalam penelitian ini menggunakan metode penelitian kualitatif deskriptif dimana peneliti akan terjun langsung ke lapangan untuk melakukan wawancara, observasi dan dokumentasi. Kepada mereka yang mengetahui dan menguasai masalah adat mangundu mantu serta bagaimana perspektif hukum Islam tentang adat mangundu mantu di Desa Tanamon Kecamatan Sinonsayang Kabupaten Minahasa Selatan. Hasil penelitian dalam skripsi ini membahas tentang adat mangundu mantu adalah suatu upacara penyambutan pengantin wanita yang datang ke rumah atau sabuah (kanopi sebagai tempat berkumpulnya keluarga mempelai pria). Dalam pelaksanaannya prosesi pernikahan masyarakat Bantik Desa Tanamon, pesta utamanya dilaksanakan dirumah mempelai wanita. Setelah itu, kedua mempelai (baik wanita dan pria) pergi ke rumah mempelai pria, jika rumahnya jauh bisa menggunakan kendaraan tetapi pada jarak kurang lebih 200 meter kedua mempelai harus turun bersama dengan iring-iringan pengantin. Kemudian menunggu keluarga mempelai pria yang secara bergantian menarik mempelai wanita dengan berjabatan tangan dan memberikan hadiah berupa uang maupun barang berharga lainnya dan berjalan selangkah demi selangkah hingga tepat di pintu masuk ke rumah mempelai pria.